(untitled) (Latakia University Journal -Basic Sciences Series, 2024)
In this work, the mixed oxide was prepared in reactive proportions by hydrothermal method. The samples have been treated at temperature 110 oC for 7 hours. The effect of the amount of directing agent (polyethylene glycol) on the specific surface area value of the prepared samples was studied. The highest value of the specific surface area was 378.0 m2/g at molar ratio without directing agent. when prepared by the dry method at a ratio of without directing agent using ammonium bicarbonate as a precipitating agent. Using amount of directing agent(g) the specific surface area decreased to 132.9 m2/g for the sample ,p(0.10g). when The amount of directing agent was increased the size of the mesoporous was increased, and the specific surface area ( increased to maximum 325.9 m2/g for the sample ,p(0.4g(